Desenvolvimento embrionário de Rhamdia quelen proveniente de fêmeas alimentadas com rações suplementadas com ácido fólico - Gonzalez, Micáila Bolzon (2023)
Nutritional supplementation of broodstock can be a strategy to improve the quality of fry in the market, as the deposition of a more nutritionally rich yolk could better meet the needs of embryos and larvae. Studies have proven that folic acid plays a role in DNA formation, erythropoiesis, protein synthesis, and embryonic development in different species. This work aims to evaluate the effect of folic acid on the development of embryos from female Rhamdia quelen fed with folic acid. A total of 540 R. quelen fry (3.71±0.01g) were housed in 18 cages with dimensions of 4x2x1m and with a mesh size of 15mm, installed in two dug ponds lined with masonry (200m²) and with an earthen bottom. The fish were fed diets containing six levels of folic acid inclusion: 0.00; 0.75; 1.50; 2.25; 3.00 and 3.75 mg of folic acid. The experiment lasted for 300 days. At the beginning of spring, the fish were classified by gender. The 270 females (155.70±1.97 g) were housed among the cages, where they began to be fed twice a day with their respective treatments. Upon reaching sexual maturity, five females from each cage underwent artificial reproduction protocol with CPE for oocyte collection and fertilization. A pool of 5ml of oocytes from each female per treatment was fertilized with an inseminating dose of 100,000 motile sperm per oocyte. The eggs were activated in 2000ml containers with the addition of 200ml of water. Egg samples were collected with a 10ml pipette and transferred to 10ml bottles with formalin buffered with calcium carbonate at 4%. During the 36 hours post-fertilization (HPF), samples were collected at specific times. The data were submitted to Analysis of Variance (ANOVA) main effects and Duncan’s multiple comparison test for mean comparisons. The offspring from females who received 3.00 mg of folic acid kg 1 were those that had an acceleration (p<0.05) in neurula and pharyngula stages and the highest percentage of normality. The abnormalities found may contribute to future studies in fish ontogenetic development. Folic acid improved embryo development, therefore, supplementation at this dose is recommended for Rhamdia quelen broodstock.